2002
DOI: 10.1074/jbc.m205117200
|View full text |Cite
|
Sign up to set email alerts
|

Mice Expressing the Human CYP7A1 Gene in the Mouse CYP7A1 Knock-out Background Lack Induction of CYP7A1 Expression by Cholesterol Feeding and Have Increased Hypercholesterolemia When Fed a High Fat Diet

Abstract: Cholesterol 7␣-hydroxylase (CYP7A1) catalyzes the rate-limiting step in the pathway responsible for the formation of the majority of bile acids. Transcription of the gene is regulated by the size of the bile acid pool and dietary and hormonal factors. The farnesoid X receptor and the liver X receptor (LXR) are responsible for regulation by bile acids and cholesterol, respectively. To study the effects of dietary cholesterol and fat upon expression of the human CYP7A1 gene, mice were generated by crossing trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
49
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(55 citation statements)
references
References 41 publications
5
49
0
Order By: Relevance
“…In both studies, wild-type mice responded to dietary cholesterol by up-regulating Cyp7a1 (5,8). In one study, dietary cholesterol did not up-regulate the human transgene (8); whereas, in the other study, the transgene was down-regulated (5). In both studies the authors suggested that humans are more responsive to dietary cholesterol than mice, because they cannot up-regulate Cyp7a1 activity in response to dietary cholesterol.…”
mentioning
confidence: 81%
See 2 more Smart Citations
“…In both studies, wild-type mice responded to dietary cholesterol by up-regulating Cyp7a1 (5,8). In one study, dietary cholesterol did not up-regulate the human transgene (8); whereas, in the other study, the transgene was down-regulated (5). In both studies the authors suggested that humans are more responsive to dietary cholesterol than mice, because they cannot up-regulate Cyp7a1 activity in response to dietary cholesterol.…”
mentioning
confidence: 81%
“…However, if this were true, then one would expect dietary cholesterol to increase plasma cholesterol levels in human Cyp7a1 transgenic mice on the mouse Cyp7a1 KO background. Yet, in the one study that made this measurement, 2% dietary cholesterol failed to increase plasma cholesterol in these animals or in wild-type mice (8). This brings into question the relevance of dietary cholesterol regulation of Cyp7a1 in plasma cholesterol responsiveness and suggests the existence of other important regulatory processes.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…The ability of LXR to induce Cyp7a1 in mice and rats makes these animals extremely resistant to a high cholesterol diet whereas other species, including man, rapidly develop hypercholesterolemia under comparable conditions. Accordingly, high cholesterol-fed mice that transgenically express human CYP7A1 in a mouse Cyp7a1 knockout background lack induction of CYP7A1 and become hypercholesterolemic [66,67].…”
Section: Nuclear Receptor Regulation Of Cholesterol Biosynthesis and mentioning
confidence: 99%
“…The ability of LXR to induce Cyp7a1 in mice and rats makes these animals extremely resistant to a high cholesterol diet whereas other species, including man, rapidly develop hypercholesterolemia under comparable conditions. Accordingly, high cholesterol-fed mice that transgenically express human CYP7A1 in a mouse Cyp7a1 knockout background lack induction of CYP7A1 and become hypercholesterolemic [66,67] Similar to FXR, CAR and PXR promote metabolism and excretion of bile acids.They partly do so by inducing the same target genes including the canalicular bile acid transporter multidrug-resistance-associated protein 2 and 3 (MRP2/ABCC2 and MRP3/ABCC3) [80][81][82]. However, the xenosensors also increase alternate, compensatory pathways for lowering hepatic bile acid levels by inducing their hydroxylation, conjugation and subsequent excretion via blood and urine [50,51,54,55,83].…”
mentioning
confidence: 99%